Longitudinal evaluation of liver stiffness in three pediatric patients with veno‐occlusive disease. (13th May 2019) - Zama, Daniele; Bossù, Gianluca; Ravaioli, Federico; Masetti, Riccardo; Prete, Arcangelo; Festi, Davide; Pession, Andrea
Abstract: Liver stiffness measurement by transient elastography is a non‐invasive ultrasound‐based technique used mainly for the evaluation of liver fibrosis in patients with chronic liver diseases. Some authors have suggested that it could be useful in the assessment of hepatic complications during hematopoietic stem cell transplant (HSCT), especially veno‐occlusive disease (VOD) or sinusoidal obstructive syndrome (SOS). Here, we present the evaluation of liver stiffness in three patients who developed severe hepatic VOD/SOS after HSCT. Liver stiffness measurement values were normal before transplant and afterward until the diagnosis of VOD/SOS when a dramatic increase was observed. After the VOD/SOS specific treatment, the values of stiffness showed a similar pattern of progressive reduction in all the three patients, with normalization after two weeks. In this report, we discuss the role of LSM in the management of patients after the diagnosis of VOD/SOS.